Identification and Characterization of White Seeded Sponge Gourd (Luffa cylindrica Roem.) Genotype under Hot-arid Region - Choudhary, B. R.; Ram, H.; Maheshwari, S. K.; Kumar, Naresh; Singh, Dhurendra (International Journal of Bio-resource and Stress Management, 2025)
The field experiment was conducted during kharif (July–November, 2022; July–November, 2023) and Spring-Summer (February–May, 2022 and February–May, 2023) seasons at research farm of ICAR-Central Institute for Arid Horticulture, Beechwal, Bikaner, Rajasthan, India to evaluate and characterize the sponge gourd genotypes to identify trait-specific genotypes. Sixteen sponge gourd genotypes were assessed for morphological performance and some qualitative traits. Substantial variations for days to 50% female flowering, days to first harvest, fruit length, fruit weight and fruit yield plant-1, were recorded. Days to 50% female flowering and days to first harvest were varied as 38.33–67.67 and 46.33–67.67, respectively. Similarly, fruit length, fruit weight and fruit yield plant-1 were ranged in 13.04–28.43 cm, 73.78–116.78 and 0.67–2.82 kg, respectively. The results of clustering indicated that all genotypes were separating in four groups. This collection of sponge gourds would be useful for the gene pools and a wide range of phenotypic variations to provide a good source of diversity for developing of sponge gourd cultivars in breeding programs. Ovate, reniform and orbicular leaf shapes; light green, medium green, dark green and green with stripes fruit skin colours; elliptical, elongate slim, elliptical elongate fruit shapes were observed among the genotypes. Genotype AHSG-23 was having the white coloured seeds at maturity while all the genotypes were having black colour seeds. This trait was stable as studied in four different environments. Therefore, white seeded AHSG-23 might be utilized as a trait-specific genotypes and the trait would be morphological marker in breeding programmes.